FORMATION OF SCALE PROPERTIES FOR ITS FULL REMOVAL FROM THE ROLLED WIRE SURFACE BEFORE WIRE DRAWING - A. B. Sychkov; M. A. Zhigarev; S. Yu. Zhukova; A. V. Perchatkin; V. I. Gritsayenko (Литьë и металлургия)
The results of investigation of chemical descaling at different temperatures of coil formation both for lowand high-carbon rolled wire are given.